2016
DOI: 10.33961/jecst.2016.7.4.277
|View full text |Cite
|
Sign up to set email alerts
|

An Electrochemical Sensor for Hydrazine Based on <italic>In Situ</italic> Grown Cobalt Hexacyanoferrate Nanostructured Film

Abstract: There is a growing demand for simple, cost-effective, and accurate analytical tools to determine the concentrations of biological and environmental compounds. In this study, a stable electroactive thin film of cobalt hexacyanoferrate (Cohcf) was prepared as an in situ chemical precipitant using electrostatic adsorption of Co 2 + on a silicate sol-gel matrix (SSG)-modified indium tin oxide electrode pre-adsorbed with [Fe(CN) 6 ] 3 − ions. The modified electrode was characterized by scanning electron microscopy,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…4. STEM-EDX elemental composition analysis of MoO agent the metal precursors were reduced into sub-2 nm sized Pt MDs and stabilized/embedded by the silicate layer since the 3D silicate sol-gel matrices are well-known candidates for offering a stable environment for metal NPs [24][25][26][27][28][29][30][31]. In addition, porous channels of the silicate layer would enhance mass transport from a electrolyte and electronic access between bare MoO 3 and Pt.…”
Section: The Growth Mechanismmentioning
confidence: 99%
“…4. STEM-EDX elemental composition analysis of MoO agent the metal precursors were reduced into sub-2 nm sized Pt MDs and stabilized/embedded by the silicate layer since the 3D silicate sol-gel matrices are well-known candidates for offering a stable environment for metal NPs [24][25][26][27][28][29][30][31]. In addition, porous channels of the silicate layer would enhance mass transport from a electrolyte and electronic access between bare MoO 3 and Pt.…”
Section: The Growth Mechanismmentioning
confidence: 99%
“…20 Ultimately, electrodeposition technique would come into the picture and due to the intricacy of the electrode/electrolyte boundary and nonuniformity of the resultant materials; shape-controlled electrodeposition remains a prodigious task. However, for specific applications, e.g., miniature device and sensor platforms are in need of active immobilization, good electrical contact and crystal facets exposed onto the substrates.…”
Section: Introductionmentioning
confidence: 99%
“…However, for specific applications, e.g ., miniature device and sensor platforms are in need of active immobilization, good electrical contact and crystal facets exposed onto the substrates. Thus, straight forward deposition of nanomaterials onto the solid support is more reasonable rather than processing with the solution phase synthesized nanomaterials . Ultimately, electrodeposition technique would come into the picture and due to the intricacy of the electrode/electrolyte boundary and non‐uniformity of the resultant materials; shape‐controlled electrodeposition remains a prodigious task.…”
Section: Introductionmentioning
confidence: 99%
“…Extensive research has shown the utility of gold (Au), platinum (Pt) and AuPt alloy nanoparticles (NPs) as the highly active and stable catalytic materials for various applications [13][14][15][16]. In particular, AuPt NPs are of widely studied as catalysts for fuel cells, hydrogenation and oxidation of organic compounds, degrading the environment pollutants and electrochemical oxidation of small organic molecules which are suitable for fuel cell applications [10].…”
Section: Introductionmentioning
confidence: 99%